Systematic review and benchmarking of Quality-Adjusted Time Without Symptoms or Toxicity (Q-TWiST) in oncology. (4th May 2018) - Solem, Caitlyn T.; Kwon, Youngmin; Shah, Ruchit M.; Aly, Abdalla; Botteman, Marc F.
ABSTRACT: Introduction : The Quality-Adjusted Time Without Symptoms or Toxicity (Q-TWiST) has been used to evaluate the clinical benefits and risks of oncology treatments. However, limited information is available to interpret and contextualize Q-TWiST results. Areas covered : A systematic review of Q-TWiST literature was conducted to provide contextualizing benchmarks for future studies. 51 articles with 81 unique Q-TWiST comparisons were identified. The mean (95% CI) and median absolute Q-TWiST gains for treatment versus control arms were 2.78 (1.82–3.73) months and 2.20 months across all cancers, respectively. The mean (median) relative Q-TWiST gains were 7.8% (7.2%) across all cancers. Most (88%) studies reported positive gains. The percentage of studies with relative Q-TWiST gains ≥10% (ie, clinically important difference) and ≥15% (ie, clearly clinically important difference) were 40.0% and 22.7%, respectively. Expert commentary : The relevance of Q-TWiST in assessing net clinical benefits of cancer therapy has not diminished, despite an arguably low number of published studies. The interest in such assessment is highlighted by the recent emergence of oncology value frameworks. The Q-TWiST should be compelling to clinicians as it integrates clinical information (ie, toxicity, relapse/progression, and survival) and patient preferences for each of these states into a single meaningful index.